A Word-frequency Based Assessment of English as a Foreign Language Master One Students' Written Receptive and Productive Lexical Knowledge - ALMI, Yahia (Journal of Human Sciences, 2017)
Learning an adequate knowledge of words is a prerequisite for linguistic mastery.     The present study was basically carried out to quantitatively evaluate EFL Master One students’ lexical knowledge. Its main objective was to assess and compare learners’ receptive and productive written word knowledge as two prominent dimensions of       a person's vocabulary knowledge recognised in many lexical researches. The study deployed two well-known frequency-based assessment tools. The first was the Vocabulary Size Test (VST) employed to measure the participants’ abilities to recognize and comprehend meanings of forms at different frequency levels within given limited contexts. The second was the Productive Vocabulary Levels Test (PVLT) primarily used to assess the participants' abilities to retrieve and produce lexical items of varying frequency levels within diverse contexts. The two tests were taken by a randomly chosen sample of 40 first year Master One students at       the Department of English at the University of Constantine 1. The results of the VST revealed that the majority of the participants’ receptive vocabulary sizes ranged between 5,000 and 8,000 word families, sizes classified as mid-frequency vocabulary. The data collected from the PVLT, comparatively, revealed a poor mastery of the participants’ abilities to use words productively in diverse contexts. Accordingly, the highest scores were achieved only in using the high-frequency vocabulary, and then they sharply decreased at lower frequency levels. Keywords: lexical proficiency, vocabulary receptive knowledge, vocabulary productive knowledge, frequency-levels, vocabulary size.